Applying Wattpad Platform as an Instruction Medium to Improve Reading Skills Viewed from Reading Strategies - Siti Nurdiana; Sudirman Sudirman; Manal Laaribi; Nguyen Thi Hong Chuyen (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
The use of Wattpad platform as an instructional medium can be a vital tool for teachers to facilitate students' reading comprehension skills. By employing effective reading strategies, students can comprehend texts more efficiently. This study aims to enhance students' reading proficiency in narrative texts by utilizing Wattpad platform as a medium, and to evaluate the students' perception of the platform's effectiveness in teaching narrative texts. This research followed a classroom action research (CAR) design, which involved the researcher, collaborators, and tenth-grade students from senior high schools. The CAR process consisted of planning, action, observation, and reflection. The research data were both qualitative and quantitative. Quantitative data was gathered from the post-test, while qualitative data was obtained through observation. The researcher employed SPSS software to analyze the quantitative data. The results showed that the mean score of the post-test was 84, indicating that the Wattpad platform application method can enhance students' reading proficiency in narrative texts. This was further confirmed by field notes and observation sheets of the teaching process, indicating that the students enjoyed the reading class and their reading abilities had improved. Moreover, the students perceived the use of Wattpad platform as very effective, with a response rate of 48 students answering (A) very good. The students' focus, drive, earnestness, and responses were deemed satisfactory, with continuous improvement in their self-assurance and reading proficiency. The educational activities were found to be interesting, suggesting that the use of Wattpad platform as an instructional medium can be beneficial for enhancing students' reading skills.